An Improved Grid-Based Energy Efficient Load Balanced Clustering Scheme in WSN - Karthika, P; Mathimalar, V (International Journal of Computer Sciences and Engineering, 2025)
In remote sensor network, clustering is used as an intense system to achieve scalability, self-organization, power saving, channel access, directing etc.. Lifetime of sensor hubs decides the lifetime of the system and, is crucial for the detecting capability.. Clustering is the key system used to develop the lifetime of a sensor network. Clustering can be used for load balancing to develop the lifetime of a sensor system by reducing vitality consumption. Load balancing utilizing clustering can too increment system scalability. Remote sensor system with the hubs with distinctive vitality levels can prolong the system lifetime of the system and, too its reliability. In this paper we propose a clustering system which will parity the load among the cluster by utilizing some reinforcement nodes. The reinforcement high vitality and, high handling power hubs replace the cluster head after the cluster reaches to its limit. This approach will increment the system lifetime and, will give high throughput.